Evaluation of Professional Development Programs Eligible for Teacher’s Professional License from the Point of View of Teachers in the State of Qatar - Nosair, Mohammad Ragab; Hendawi, Manal; El Rous, Adel Abo (Dirasat: Educational Sciences, 2023)
Objectives: This study evaluates professional development programs leading to qualified teacher status from the perspective of teachers in the State of Qatar. It considers various variables, including gender (male/female), nationality, profession, educational qualification, years of experience, educational stage, and specialization. Methods:The study used a questionnaire to assess the satisfaction of 2125 male and female teachers at all educational levels in Qatar with the training program. The questionnaire measured satisfaction in four areas: training content, trainer, training procedures, and training environment. The program was developed by the Ministry of Education and Higher Education in collaboration with the College of Education at Qatar University to prepare teachers for their professional status. Results: The study revealed a high level of teacher satisfaction with the training program leading to qualified teacher status in Qatar. Moreover, there were no statistically significant differences in satisfaction levels based on nationality, occupation, educational qualification, specialization, or years of experience. Conclusions: The study emphasizes the importance of designing training programs for qualified teacher status in Qatar according to teachers’ actual training needs to enhance participant satisfaction and program effectiveness. It also recommends continuous training of teachers to meet the standards for qualified status in Qatar, improving the training environment, and leveraging modern technologies in education.